Managerial Incentives and the Valuation of International Joint Venture Formation - Wild, John J; Wild, Jonathan M; Wild, Kenneth L (Journal of Accounting, Business and Finance Research, 2022)
Strategic management decisions and actions involving international joint venture formations are significant to many firms and have major economic consequences. Previous empirical evidence on the effects of joint venture formation announcements on shareholder wealth reveals that firm value is more often positively impacted. However, many previous analyses of shareholder wealth from joint venture formations do not fully explore cross-sectional differences in managerial incentives to pursue these international investments. The primary purpose of this study is to exploit these cross-sectional differences using agency theory to explain managerial behavior and subsequent shareholder effects. This study capitalizes on agency theory’s notion that managers are not necessarily motivated solely by the maximization of firm value, but instead are interested in maximizing their own utility. The study’s findings are consistent with agency theoretic hypotheses based on a broad cross-section of international joint ventures. Results demonstrate that shareholder returns to international joint venture formation exhibit considerable variability and, importantly, are at least partially explained by cross-sectional differences in agency incentives. Specifically, returns to shareholders are positively related to the level of managerial ownership and inversely related to the level of free cash flow. Moreover, a positive relation is found between shareholder returns and the joint interaction between leverage and free cash flow. These findings indicate that the effect of international joint venture formation on shareholder value is not uniform and, more importantly is at least partly influenced by managers’ agency incentives.